Pharmacological inhibition of C-C chemokine receptor 4 aggravates atherosclerosis through prevention of regulatory T cell recruitment to the lesions. (25th November 2020) - Amin, H; Sasaki, N; Horibe, S; Kawauchi, S; Hirata, K; Rikitake, Y
Abstract: Background: Regulatory T cells (Tregs) are demonstrated to play a protective role in the development of atherosclerosis. However, their sites of action in atherosclerosis remain unclear. Although C-C chemokine receptor 4 (CCR4) has been shown to contribute to the accumulation of Tregs in inflamed tissues and prevention of experimental autoimmune diseases, the role of CCR4 in Treg migration to atherosclerotic lesions and suppression of plaque formation remains unknown. Methods and results: We intraperitoneally injected 8-week-old apolipoprotein E–deficient mice fed a normal diet with vehicle (n=9) or a 4-μg dose of a CCR4 antagonist (n=10) 3 times weekly for 8 weeks and evaluated atherosclerotic lesions at 16 weeks old. Administration of the CCR4 antagonist significantly aggravated atherosclerotic plaque formation (aortic sinus plaque area: 2.91±0.87×104 μm 2 versus 5.41±0.98×104 μm 2 in control vehicle-treated and CCR4 antagonist-treated mice, respectively; P<0.05), associated with increased accumulation of macrophages and CD4+T cells in the plaques. Flow cytometric analysis revealed a decrease in Foxp3+ Tregs in the para-aortic lymph nodes and thoracoabdominal aortas of CCR4 antagonist-treated mice, along with a tendency toward increase in CD44highCD62Lloweffector T cells in para-aortic lymph nodes, indicating CCR4-dependent migration of Tregs to atherosclerotic lesions and their possible atheroprotective role. We observed no changes in splenic Foxp3+ Tregs and effector T cells following CCR4 antagonist treatment. We also investigated the effect of CCR4 blockade on advanced atherosclerosis using LDL receptor–deficient mice fed a high-cholesterol diet. Although 8-week treatment with the CCR4 antagonist led to a decrease in Foxp3+ Tregs in the atherosclerotic lesions, atherosclerotic lesion formation was not significantly affected, suggesting that CCR4-dependent Treg accumulation in atherosclerotic lesions is not critical for prevention of advanced atherosclerosis. Conclusions: Our findings indicate an important role for CCR4 in promotion of Treg recruitment into atherosclerotic lesions and subsequent prevention of early atherosclerosis and suggest CCR4 as a novel therapeutic target for atherosclerosis. Funding Acknowledgement: Type of funding source: None